Transformasi Bisnis Media Cetak di Era Digital PASKAM (Persatuan Agen Surat Kabar dan Majalah) Kota Bandung - Sutrisno, Sutrisno; Nurjaman, Kiki; Tunaerah, Linda (Edumedia Solution, 2024)
This service aims to provide socialization on the use of smartphone applications as a digital promotional tool for newspaper and magazine delivery businesses on Jl. Cikapundung, Bandung City. The Bandung City newspaper delivery association is the target of newspaper media promotion. Tourism businesses have difficulty directing digital promotions to the upper middle class. Partners have limitations in using smartphones to edit photos, and videos and use social media. This activity adopts a contextual approach method by providing theory, direct practice in editing photos and videos, as well as guidelines for using social media. Instructors carry out practice with partners to strengthen their understanding of news editing marketing applications and online advertising. The transformation of the print media business to the digital era is emphasized. Partners are expected to be able to improve their capabilities in digital promotions.